Assembling the (Non)Human: The Animal as Medium (Imaginations: Journal of Cross-Cultural Image Studies, 2018)
Abstract | This article revisits McLuhan’s well-known phrase “the message is the medium,” and it asks: What if the medium is an animal?  McLuhan’s understanding of his own phrase was profoundly anthropocentric, as critics have noted. But his legacy in mediation theory combined with the insights of interdisciplinary animal studies make it possible to expand the possibilities of the phrase.  Media history also challenges the anthropocentric concept of the medium or the mediation process.  While the use of animal as medium predates the electric media with which McLuhan was concerned,  early computer devices and later mobile technologies have pursued users’ engagement through didactically visible identification with/as animal spirits.  Animals have become “naturalized” along with the indispensability of these devices as essential mediators of connectivity.  In contemporary media arts, we see animals mediate and metaphorically stand for the vitality of mediated connectivity.  Recognizing animal figures as mediators of mediation shifts the balance, the affect, and the price of what McLuhan called our “shared media situation.” They are both luring enchantments into digital connectivity and anxious premediations of rising challenges to anthropocentric humanism and its destructive blind spots which continue to shape the world.Résumé | Cet article revisite la phrase bien connue de McLuhan « le message est le médium », et il demande : et si le médium est un animal? La compréhension de McLuhan de sa propre phrase était profondément anthropocentrique, comme les critiques l’ont noté. Cependant, son héritage dans le domaine de la théorie de la médiation, combiné avec les connaissances des études interdisciplinaires sur les animaux, permet d’élargir les possibilités de la phrase. L’histoire des médias remet également en cause le concept anthropocentrique du médium ou du processus de médiation. Bien que l’utilisation de l’animal comme médium soit antérieure aux médias électriques dont parlait McLuhan, les premiers dispositifs informatiques et les technologies mobiles subséquentes ont poursuivi l’engagement des utilisateurs grâce à une identification didactiquement visible avec/comme des esprits des animaux. Les animaux sont devenus « naturalisés », parallèlement au caractère indispensable de ces dispositifs comme médiateurs essentiels de la connectivité. Dans les arts médiatiques contemporains, nous voyons les animaux faire de la médiation et métaphoriquement représenter la vitalité de la connectivité médiée. Reconnaître les figures animales comme médiateurs de la médiation modifie l’équilibre, l’effet, et le prix de ce que McLuhan appelle notre « situation médiatique partagée ». Ils entraînent à la fois un ensorcellement vers la connectivité numérique et des préméditations anxieuses des défis croissants de l’humanisme anthropocentrique et de ses angles morts destructeurs qui continuent à façonner le monde.